Intrasubband plasmons in a weakly disordered array of quantum wires - Bludov, Y.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
A theoretical investigation is carried out for plasmons in a weakly disordered array of quantum wires, consisting of a finite number of quantum wires arranged at an equal distance from each other. The array of quantum wires is characterized by the fact that the density of electrons of one "defect" quantum wire was different from that of the other quantum wires. It is assumed that the defect quantum wire can be arranged at an arbitrary p osition in the array. The existence of a local plasmon mode, whose properties differ from those of usual modes, is found. It is pointed out that the local plasmon mode spectrum is slightly sensitive to the position of the defect quantum wire inthe array. At the same time the spectrum of usual plasmon modes is shown to be very sensitive to the position of the defect quantum wire.